2011
DOI: 10.1111/j.1464-5491.2011.03325.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of capillary abnormalities in patients with diabetes and association with retinopathy

Abstract: A high prevalence of nailfold capillary changes is detected in patients with diabetes using nailfold videocapillaroscopy. These abnormalities tightly correlate with retinal damage and may be expression of a generalized microvessel involvement in both Type 1 and Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 16 publications
5
61
0
2
Order By: Relevance
“…This vascular heterogeneity may be related to significant autonomic neuropathy disturbances among population with this disease. Some other reports confirmed our results [2] [16].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This vascular heterogeneity may be related to significant autonomic neuropathy disturbances among population with this disease. Some other reports confirmed our results [2] [16].…”
Section: Discussionsupporting
confidence: 83%
“…Kaminska-Winciorek et al also showed an increased frequency of twisted capillaries in patients with diabetes type 1 and 2 [4]. Although we did not consider duration of disease, coiled capillaries were significantly reported in patients with diabetes with long-standing disease [18]. Of all participants 17% had different degrees of advanced microcirculation angiopathy (scleroderma pattern) that warned us for more attention against consequence complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27][28] No subjects had manifest diabetic retinopathy, which may indicate systemic microvasculopathy. 29 XFS/XFG patients demonstrated XFM on slit lamp examination by an ophthalmologist at recruitment. POAG patients had no secondary cause for elevated IOP on anterior segment examination and no secondary cause for optic nerve disease on posterior segment examination.…”
Section: Study Design and Samplementioning
confidence: 99%